2020
DOI: 10.4236/eng.2020.122007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between the Number of Traffic Accidents and the Traffic Flow & Section Location in Extra Long Tunnel

Abstract: In order to study the influence of the traffic characteristics on traffic accidents in extra long tunnel, the main measurement indicators of traffic flow during the time of traffic accidents are matched with the accident information to form a data set of the number of traffic accidents and the hourly traffic flow of the accident. Vehicle ratio and the number of accidents are mainly used as the characteristic indicators of traffic flow. At the same time, the longitudinal distribution law of the average speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…To avoid interference of the drivers by traffic flow as much as possible, the experimental period is selected in the common period (9 am to 11 am and 2 pm to 4 pm). From the traffic accident statistics of the whole tunnel, there are more traffic accidents at the entrance and exit sections [8]. One of the main reasons is that the illumination inside and outside the tunnel is quite different, and the "black hole effect" at the entrance and the "white hole effect" at the exit are more serious.…”
Section: Experiments Time and Drivermentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid interference of the drivers by traffic flow as much as possible, the experimental period is selected in the common period (9 am to 11 am and 2 pm to 4 pm). From the traffic accident statistics of the whole tunnel, there are more traffic accidents at the entrance and exit sections [8]. One of the main reasons is that the illumination inside and outside the tunnel is quite different, and the "black hole effect" at the entrance and the "white hole effect" at the exit are more serious.…”
Section: Experiments Time and Drivermentioning
confidence: 99%
“…This change process and related phenomena will directly affect the driving ability of the driver [7]. Under the interaction of the longitudinal slope and illumination changes, drivers will face greater challenges in behavior and psychology, which will lay hidden dangers for driving safety [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this research, a complete undersea tunnel is divided into the approach section, entrance section, middle section, exit section, and departure section [29], [30]. The exit and entrance sections are divided into lane change, transition and adaptation sections [31]. A schematic of the undersea tunnel division is shown in Figure 1.…”
Section: Division Of Entrance and Exit Sections Of The Undersea Tunnelmentioning
confidence: 99%
“…The study also indicated a higher risk of collisions at tunnel entrances. To study the influence of traffic characteristics on traffic accidents in extra-long tunnels, Ma [26] matched the primary traffic volume measurement indicators at the time of traffic accidents with accident information to form the number of traffic accidents and traffic accident datasets. Concurrently, he discovered that the form of traffic accidents in super-long tunnels was dominated by rear-end collisions.…”
Section: Introductionmentioning
confidence: 99%